2004
DOI: 10.1002/ajh.20162
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of bleeds in hemophilia patients with inhibitors: Emerging data and clinical direction

Abstract: In patients with hemophilia, the development of high-responding inhibitors to factor VIII prevents adequate replacement therapy and results in increased risk of serious bleeding episodes, poor control of joint bleeding, and progressive, debilitating joint disease. Immune tolerance therapy can eradicate inhibitors, but it is not uniformly successful. Emerging data suggest that prophylaxis using activated prothrombin complex concentrates may be effective and safe in reducing the incidence of joint bleeding durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 42 publications
1
103
0
Order By: Relevance
“…Consistent with the current case report, two of the previous studies also found decreased inhibitor titers during FEIBA prophylaxis [8,10]. Notably, studies by Escuriola-Ettingshausen et al [9], Valentino and Salit [12], and Leissinger [7] also showed maintenance or improvement of existing arthropathy. In the present patient, effects of FEIBA on arthropathy could not be determined, as he had no joint disease at the start of FEIBA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the current case report, two of the previous studies also found decreased inhibitor titers during FEIBA prophylaxis [8,10]. Notably, studies by Escuriola-Ettingshausen et al [9], Valentino and Salit [12], and Leissinger [7] also showed maintenance or improvement of existing arthropathy. In the present patient, effects of FEIBA on arthropathy could not be determined, as he had no joint disease at the start of FEIBA.…”
Section: Discussionsupporting
confidence: 90%
“…FEIBA also has been used for prophylaxis during immune tolerance induction [6]. Regular prophylactic replacement with PCC or APCC, however, has not been used routinely in inhibitor-positive patients in the United States, as controlled trials of prophylaxis have not been conducted and there is no consensus on standard dosing [7]. There are several reports on the efficacy for prevention of bleeding by PCC or APCC in patients with inhibitors [6,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…1 The development of high-titer factor VIII inhibitors (>5 Bethesda units [BU]) complicates treatment because bleeding no longer responds to standard factor VIII replacement. 2,3 Alternative forms of clottingfactor concentrates, known as bypassing agents, are used to treat bleeding in these patients. 3 Two bypassing agents are currently available: anti-inhibitor coagulant complex (AICC) and recombinant activated factor VII (rFVIIa).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Alternative forms of clottingfactor concentrates, known as bypassing agents, are used to treat bleeding in these patients. 3 Two bypassing agents are currently available: anti-inhibitor coagulant complex (AICC) and recombinant activated factor VII (rFVIIa). Both agents control approximately 80% of bleeding episodes in patients with hemophilia and inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In Dr. DiMichele's own words, "there is too much left to do." [43,44], acquired hemophilia A [45], and other coagulation disorders, such as von Willebrand disease. She has been an active investigator for numerous research studies and Principle Investigator for 2 investigator-initiated, multiinstitutional clinical trials of treatments for individuals with hemophilia A and factor VIII inhibitors: the Rituximab for Inhibitors in Congenital Hemophilia (RICH) study [46] and the ProFEIBA study of anti-inhibitor coagulant complex prophylaxis [44].…”
Section: Dr Hsieh's Perspectivementioning
confidence: 99%